ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKTIVITAS DAN KELAYAKAN USAHATANI PADI SAWAH - Carolus Oktavius Rudianto Laim; Liska Simamora (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This research aims to analyze the production inputs (production capital, seeds, land area, labor, fertilizer, pesticide) that affect production and farming feasibility toward the productivity of rice field farming in Wonotoro Kecamatan Sambi Boyolali village. The data of this quantitative research was collected by using interview where the questions were written inside the questionnaires which have been distributed to the sample of this research. The sample was taken using Probability sampling technique with simple random sampling method. This research has 70 rice farmers as the respondents. The data were analyzed by using Cobb - Douglass production function. The result showed that the production function of land area and labor had a significant effect on productivity, while the production factors of capital, seeds, fertilizers, and pesticides had an effect on productivity. The result of the rice - field farming feasibility analysis shows that R/C ratio is 1,77 and B/C is 1,06. These addresses to a conclusion that farming activities is absolutely feasible because it could increase the financial aspect. The use of production capital and the right fertilizer could increase maximum result.